2018
DOI: 10.1016/j.jcin.2018.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Trends and Comparative Outcomes With Adjunctive Inferior Vena Cava Filter Placement in Patients Undergoing Catheter-Directed Thrombolysis for Deep Vein Thrombosis in the United States

Abstract: This nationwide observational study suggests that one-third of all patients undergoing CDT receive IVCFs. IVCF use was not associated with a decrease in in-hospital mortality but was associated with higher inpatient charges and longer length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Limited ++** Summary of the evidence.-One randomized controlled trial and 2 observational studies met the inclusion criteria for this question (27)(28)(29).…”
Section: Strength Of Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited ++** Summary of the evidence.-One randomized controlled trial and 2 observational studies met the inclusion criteria for this question (27)(28)(29).…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Another-low quality retrospective cohort study (29) using the National Inpatient Sample database also found no significant differences in in-hospital mortality and complications such as gastrointestinal bleeding (0.7% vs 1.0%; P ¼ .20), procedure-related hemorrhage (1.4% vs 1.9%; P ¼ .17), and intracranial hemorrhage (0.7% vs 0.6%; P ¼ .70) between patients with and without an IVC filter who were undergoing catheter-directed thrombolysis. However, higher rates of hematoma formation (3.4% vs 2.1%; P ¼ .009) were found in the IVC filter group.…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…There is still controversy over the need for an IVC filer during endovascular treatment for DVT, however, there have been several reports that this is necessary [ 11 - 14 ]. Nevertheless, there are often situations where the IVC filter cannot be inserted.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies of CDT combined with IVCFs showed no difference in PE or mortality compared with CDT alone, but increased complications were noted in patients who had filters placed. 28,29 Conversely, the FILTER-PEVI RCT demonstrated that IVCFs lowered the incidence of immediate post-procedural symptomatic PE without mortality benefit compared with patients receiving anticoagulation alone. 30 The authors advised a selective approach to filter placement in those with specific predictors of PE.…”
Section: Other Extended Indicationsmentioning
confidence: 99%